Building a Hybrid Systems Modeler on Synchronous Languages Principles - Benveniste, Albert; Bourke, Timothy; Caillaud, Benoit; Colaco, Jean-Louis; Pasteur, Cedric; Pouzet, Marc (Proceedings of the IEEE, 2018)
Hybrid systems modeling languages that mix discrete and continuous time signals and systems are widely used to develop cyber-physical systems where control software interacts with physical devices. Compilers play a central role, statically checking source models, generating intermediate representations for testing and verification, and producing sequential code for simulation and execution on target platforms. This paper presents a novel approach to the design and implementation of a hybrid systems language, built on synchronous language principles and their proven compilation techniques. The result is a hybrid systems modeling language in which synchronous programming constructs can be mixed with ordinary differential equations (ODEs) and zero-crossing events, and a runtime that delegates their approximation to an off-the-shelf numerical solver. We propose an ideal semantics based on nonstandard analysis, which defines the execution of a hybrid model as an infinite sequence of infinitesimally small time steps. It is used to specify and prove correct three essential compilation steps: 1) a type system that guarantees that a continuous-time signal is never used where a discrete-time one is expected and conversely; 2) a type system that ensures the absence of combinatorial loops; and 3) the generation of statically scheduled code for efficient execution. Our approach has been evaluated in two implementations: the academic language Zélus, which extends a language reminiscent of Lustre with ODEs and zero-crossing events, and the industrial prototype Scade Hybrid, a conservative extension of Scade 6.